Music motivation and the effect of writing music: A comparison of pianists and guitarists. (May 2014) - MacIntyre, Peter D.; Potter, Gillian K.
The purpose of this study is to examine a set of motivation variables within guitar and piano players. We also tested for motivational differences among three groups: those who write music, those who plan to write music in the future, and those who do not write nor intend to write. An international sample of 599 musicians was obtained (guitar: N = 292, piano: N = 307) through the use of an online survey. Self-Determination Theory, a prominent perspective in the motivation literature, was utilized along with other motivational constructs, including perceived competence, musical self-esteem, effort, desire to learn, willingness to play, and possible musical selves. Findings revealed differences between pianists' and guitarists' levels of motivational intensity, desire to learn, introjected regulation, perceived competence and willingness to play. Results also indicated that the group who write music had significantly higher levels of musical self-esteem, willingness to play, motivational intensity, desire to learn, and perceived competence. Findings from this study suggest that pianists and guitarists both are intrinsically motivated, but for different reasons. The underlying motivational needs that are met by the instrument's "culture" appear to focus on competence for pianists and on autonomy and relatedness for guitarists.